Tracing the Traceur - Emma Nilsson (User Experience & Urban Creativity)
This essay is a photographic exploration of parkour, tracing the experience of the traceur, reflecting upon how photography can destabilize the point of views architecture operates from, and thereby expand the narratives on architecture possible to trace through photography.